SELF-HEALING CAPACITY OF CONCRETE - COMPUTER SIMULATION STUDY OF UNHYDRATED CEMENT STRUCTURE - He, Huan; Guo, Zhanqi; Stroeven, Piet; Stroeven, Martijn; Sluys, Lambertus Johannes (Image Analysis and Stereology, 2011)
Aggregate occupies at least three-quarters of the volume of concrete, so its impact on concrete's properties is large. The aggregate's influence on the non-hydrated part of the matured paste is assessed by concurrent algorithm-based computer simulation system SPACE in this paper. A distinction is made between interfacial zones (ITZs) and bulk paste. Containers with rigid boundaries were employed for the production of series of cement pastes. They were subjected to quantitative microstructure analysis. Relevant gradient structures in the ITZ and bulk are presented and discussed. The relevance of this structure information for possible selfhealing of cracks is briefly discussed.